LITERATURE REVIEW: THE IMPACT OF AUGMENTED REALITY ON THE PROCESS - Azizah, Nur; maulana, Andrico bagus; Safitri, Undayani; Dewi, Shinta Noviana; Razaqi, Rahmat Shofan (Journal on Research and Review of Educational Innovation, 2025)
The application of Augmented Reality (AR) technology in education has been the focus of various studies due to its potential in improving the learning process. This article examines the impact of AR use on education through the Systematic Literature Review (SLR) method by analyzing 15 selected journals published in 2020-2024. The results show that AR has a significant positive impact in improving student understanding, learning motivation, as well as providing an immersive and interactive learning experience. In particular, AR helps students understand abstract concepts, strengthens memory through multisensory experiences, and improves learning effectiveness at various levels of education. However, challenges such as limited infrastructure and educator readiness remain barriers to the widespread implementation of AR. Thus, AR is a potential innovation to enrich the learning process in the digital era.